Design of Electronic Module ATS Message Handling System (AMHS) as Learning Media on Learning Management System (LMS) Aviation Polytechnic of Surabaya - Vandosyen, Winando; Hariyanto, Didi (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
The ATS Message Handling System (AMHS) electronic module was developed using the ASSURE model which is an acronym for (Analyze Learners, State Standards and Objectives, Select Methods and Strategies, Utilize Media, Require Learners Participation, and Evaluate & Revise). ASSURE is one of the simple learning designs that can create a learning that is expected to guide educators effectively, efficiently, and systematically and attractively. The aims of this research are: 1) To build and produce an electronic Module Design product ATS Message Handling System (AMHS) which can be used as learning on the Learning Management System (LMS) of Aviation Polytechnic Surabaya, 2) To determine and test the feasibility of the ATS Message Handling System (AMHS) electronic Module Design as a learning media on the Learning Management System (LMS) of the Aviation Polytechnic Surabaya. From this study it was found that the results of the Material Expert Validation Test obtained the "Valid" and "Very Understandable" categories. Then Media Validation Test 1 obtained the "Valid" and "Understandable" categories and Media Validation Test 2 obtained the "Valid" and "Very Understandable" categories, and the Learner Response Test obtained 90.4% of the "Very Good" or "Very Feasible" category. As a result, the ASSURE model in the ATS Message Handling System (AMHS) is very worthy (effective and efficient) in the context of utilizing learning on the Learning Management System (LMS) in Aviation Polytechnic of Surabaya.